2014
DOI: 10.1212/wnl.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Brain communication in a completely locked-in patient using bedside near-infrared spectroscopy

Abstract: Amyotrophic lateral sclerosis (ALS) can result in the locked-in state (LIS), characterized by paralysis, and eventual respiratory failure, compensated by artificial ventilation, 1 or the completely LIS (CLIS), with additional total paralysis of eye muscles. Brain–computer interfaces (BCIs) have been used to allow paralyzed people to regain basic communication, 2 although current EEG-based BCIs have not succeeded with CLIS patients. 3 We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 5 publications
0
85
0
1
Order By: Relevance
“…Moreover, for completely locked-in state of ALS, the current study lacks the proof of applicability as correct eye movement control and the ability to blink in this state is not given by definition [14]. Then, additional Brain-Computer Interface technology is needed, which has recently been shown to be an effective means of communication in completely locked-in ALS patients [36]. A further limitation of our study is the possible impact of some oculomotor abnormalities in patients with ALS on our results that were not controlled for.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, for completely locked-in state of ALS, the current study lacks the proof of applicability as correct eye movement control and the ability to blink in this state is not given by definition [14]. Then, additional Brain-Computer Interface technology is needed, which has recently been shown to be an effective means of communication in completely locked-in ALS patients [36]. A further limitation of our study is the possible impact of some oculomotor abnormalities in patients with ALS on our results that were not controlled for.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, with one exception (Gallegos-Ayala et al, 2014), patients lacking control of all muscles (e.g., completely locked-in patients) have been entirely unsuccessful in maintaining control over neuroimaging signals (De Massari et al, 2013).…”
Section: Megmentioning
confidence: 99%
“…BCI can be used for restoration of multiple functions including communication and motor functions; however, the most rapidly developing usage of the BCI system is for communication. Recently, Gallegos-Ayala et al 63 reported that the NIRS-based BCI system showed an above chance level classification result in a patient with amyotrophic lateral sclerosis who was in a completely locked-in-state. These findings suggested that even in a locked-in-state patient, BCI enables the provision of a communication method.…”
Section: Neural Mechanism For Postural Controlmentioning
confidence: 99%